Social scientists at work - Leathem, Jack; McLead, Doug; Slaven, Angela (Milton Keynes : Open University Worldwide, 1993)
Explain the role of social scientists. Also described the activity social scientists and how they gather and use the information. Including method of research sciences.
Keywords: Social scientists; Social sciences -- Research